A convenient route to a vinylogous dicyano aryl based AIEgen with switchable mechanochromic luminescence properties. Issue 30 (23rd March 2023) - Ghosh, Saurajit; Bhambri, Himanshi; Singh, Ajeet Kumar; Mandal, Sanjay K.; Roy, Lisa; Addy, Partha Sarathi
Abstract : A convenient two step synthetic protocol is reported to obtain a mechanochromic luminescent molecule with switchable optical property. Abstract : Molecules with solid state luminescence and mechanochromic luminescence properties have attracted immense interest owing to their potential application in the areas of organic field-effect transistors (OFETs), organic light-emitting diodes (OLEDs), optoelectronic devices, fluorescence switches, mechano-sensors and data storage. Herein we report a convenient two step synthetic protocol to obtain a couple of luminescent molecules. Using these, a comparative study has been performed to showcase the importance of the weak π⋯π interactions to observe the aggregation induced emission (AIE) and solid-state mechanochromic luminescence. The most fascinating part of this report is to observe the switchable fluorescent dark and bright states of the solid AIEgen. We have also demonstrated the use of the AIEgen to detect volatile organic compounds.